Acoustic topological circuitry in square and rectangular phononic crystals - Laforge,N; Wiltshaw,R; Craster,RV; Laude,V; Martínez,JAI; Dupont,G; Guenneau,S; Kadic,M; Makwana,MP (Physical Review Applied, 2021)
We systematically engineer a series of square and rectangular phononiccrystals to create experimental realisations of complex topological phononiccircuits. The exotic topological transport observed is wholly reliant upon theunderlying structure which must belong to either a square or rectangularlattice system and not to any hexagonal-based structure. The phononic systemchosen consists of a periodic array of square steel bars which partitionsacoustic waves in water over a broadband range of frequencies (~0.5 MHz). Anultrasonic transducer launches an acoustic pulse which propagates along adomain wall, before encountering a nodal point, from which the acoustic signalpartitions towards three exit ports. Numerical simulations are performed toclearly illustrate the highly resolved edge states as well as corroborate ourexperimental findings. To achieve complete control over the flow of energy,power division and redirection devices are required. The tunability afforded byour designs, in conjunction with the topological robustness of the modes, willresult in their assimilation into acoustical devices.